Integrating STEM education approach in enhancing higher order thinking skills - Baharin, Norlizawaty; Kamarudin, Nurzatulshima; Abdul Manaf, Umi Kalthom (Human Resource Management Academic Research Society, 2018)
The initiatives of integrating Science, Technology, Engineering and Mathematics (STEM) in the educational curriculum in schools is one of the efforts of the Ministry of Education to encourage students’ interest and involvement in STEM. 21st century teaching and learning approach to STEM is one of the keys to effective learning, meaningful and deep understanding that can integrate science, technology, engineering and mathematics among students. The process of integrating STEM can be challenging because it requires a new generation that have skills in STEM fields. The approach of STEM education should include elements of problem solving, critical thinking, creative thinking and scientific thinking that can enhance higher order thinking skills (HOTS) among students. This article discusses the importance of STEM approach in the learning and teaching process that is able to enhance thinking skills among students. There are various factors and challenges to be considered in its implementation. The approaches, strategies and models that can be used to improve thinking skills among students are also discussed.